Genetic Variation of Trichomonas vaginalis Isolates from Iraqi Women: Association with Fertility and Cervical Abnormalities (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Background: Trichomoniasis, is one of the most common non-viral sexually transmitted diseases caused by the parasite Trichomonas vaginalis. Little is known about the genetic diversity and population structure of this parasite. This study aimed to determine the genetic diversity of T. vaginalis isolated from Iraqi women and its association with the fertility and the cervical abnormalities.Methods: Overall, 154 Iraqi women attending the Gynecology Outpatient departments in Baghdad Province, Iraq from February 2013 to April 2014, were enrolled in this study. DNA of T. vaginalis isolates was extracted from the culture of high vaginal swabs. Multilocus sequence typing (MLST) method for six housekeeping genes was done in studying the genetic variations.Results: Fifty-three women (34.41%) were positive for T. vaginalis. MLST method resulted in different alleles. With glutaminase gene, the highest degree of variation was found among the six genes.Conclusion: The genetic diversity in the organism itself in Iraqi isolates can associate with clinical outcome. Further MLST studies are needed to compare a larger number of isolates from different localities and correlate the certain mutations in housekeeping genes to infertile women and patients with cervical abnormalities.